COMPARISON OF BIODIESEL PRODUCED FROM NEW AND USED COOKING OIL USING NAOH AND LOCAL ISOLATE LIPASE AS CATALYST - Nugraha, Bayu
Biodiesel is an alkyl ester compound that is used as an alternative fuel in diesel engines. Biodiesel is produced through a transesterification reaction by mixing oil and alcohol with the help of a catalyst. This research aims to study the effect of the type of oil substrate, catalyst, and reaction conditions used for biodiesel synthesis. One source of oil that can be used in the production of biodiesel is cooking oil. The production of biodiesel from used cooking oil has been widely carried out as an alternative fuel source. The used cooking oil substrate used in this study was pretreated by filtering, heating, and adding coconut fiber adsorbent. Two catalysts commonly used in biodiesel production are alkaline catalysts and lipase catalysts. In this study, biodiesel production was carried out using a base catalyst in the form of NaOH and a thermostable local isolates lipase LK2. The advantages of using lipase as a catalyst include that it can be regenerated and reused, the product separation is relatively easier, and the conversion of oil into biodiesel is more effective. The transesterification reaction with a lipase catalyst was carried out at a temperature range of 45 – 50°C for 24 hours. In this study, lipase LK2 was isolated with a concentration of 0,231 mg/mL and a specific activity of 4,210 U/mg. Then the isolated lipase is used in the production of biodiesel. Furthermore, for the transesterification reaction with a NaOH catalyst was carried out at a temperature range of 57 - 62°C for 1 - 3 hours. From the results of the analysis using the GC-MS instrument, it was found that both the reaction product sourced from new cooking oil and used cooking oil contained alkyl ester compounds with various carbon chain lengths. These results indicate that the transesterification reaction using NaOH and lipase LK2 catalysts succeeded in producing biodiesel. The optimum conditions for biodiesel production with NaOH catalyst were found at a mole ratio of oil: alcohol of 1:6 with a reaction time of 1 hour. Meanwhile, biodiesel production with LK2 lipase catalyst, the peak of the chromatogram produced by each compound is not clearly visible. This indicates the possible reaction conditions that occur using lipase LK2 are not yet optimum. The methyl ester compounds produced from the reaction using the NaOH catalyst were more diverse than the reaction using the LK2 lipase catalyst. There was no significant difference in methyl ester content for biodiesel synthesis using both new and used cooking oil.